OP0238 Association between age at diagnosis and clinical presentation and outcomes of anca-associated vasculitis. analysis from the dcvas study. (12th June 2018) - Monti, S; Craven, A.; Klersy, C.; Montecucco, C.; Caporali, R.; Watts, R.; Merkel, P.A.; Luqmani, R.
Abstract : Background: ANCA-associated vasculitis (AAV) can affect all age groups. Nevertheless, the differences in disease presentation and outcome between younger and elderly-onset patients are still incompletely understood. 2 Objectives: To identify distinguishing characteristics of clinical presentations, short-term outcomes and accumulated damage for AAV, based on age of disease onset. Methods: We included patients with a final diagnosis of AAV: granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), eosinophilic granulomatosis with polyangiitis (EGPA) enrolled in The Diagnostic and Classification Criteria for Primary Systemic Vasculitis (DCVAS) study through May 2017. We divided the population according to age at diagnosis:<65 years old (group A) or ≥65 (group B). Results: We included 1338 patients. 66% had a disease onset <65 years of age (male:50%; mean age 48.4±12.6 years); 34% had an elderly-onset (male: 46%; mean age 73.6±6). The diagnoses of GPA and EGPA were more frequent in group A (73% and 74% of patients, respectively) compared to MPA (56%), p<0.001 for comparisons within each diagnostic group. P-ANCA/anti-MPO positivity was more frequent in group B (48% vs 27%, p=0.001); c-ANCA/PR3 predominated in group A (48% vs 35%; p<0.001). The clinical presentation at onset significantly differed between the two groups. Patients from group A had higher rates of ocular, cutaneous, and musculoskeletal involvement compared to patients in group B who experienced more systemic, renal, cardiovascular, and neurological manifestations (figure 1). Pulmonary and gastrointestinal manifestations were equally distributed between the two age groups. Vasculitis Damage Index (VDI) was significantly higher in patients from group B, with 12% of patients with a 6 months VDI score ≥5, compared to 7% in group A; p=0.01. There were 13 (1.5%) deaths amongst patients belonging to group A compared to 22 (4.8%) in group B, HR 3.44 (1.65–7.18); p=0.001. Conclusions: Patients with AAV with elderly-onset disease display a different pattern of organ-involvement and an increased risk of significant damage and mortality compared to younger patients. A better understanding of the influence of age of onset on the clinical course of AAV could improve diagnostic and classification criteria and has implications on their pattern of presentation and subsequent clinical course. References: [1] Watts RA, et al. Epidemiology of systemic vasculitis. Arthritis Rheum2000;43:414–19. [2] Chen M, et al. Antineutrophil cytoplasmic autoantibody-associated vasculitis in older patients. Medicine2008;87:203–9. Disclosure of Interest: None declared